O ensino léxico-semântico de advérbios : literatura e games no ensino fundamental II - Santana, José Barbosa (2018)
The purpose of this work is to teach the Portuguese language in grammatical studies, and literature is the definitive instrument for the elaboration of an electronic game that we intend to make available in the form of mobile phone and computer applications . Our theme seeks the functional teaching of adverbs, based on lexical-semantic principles of synonymy and antonyms (MOURA; CAMBRUSSI, 2018), for students of basic education. Our population sample is delimited in the 9th year of elementary school II of a state public school in the municipality of Boquim, State of Sergipe. Our goal is to build a game (GEE, 2003), with the story "Come and see the sunset", by Lygia Fagundes Telles, so that the students can reconstruct the adverbial bases taking into account their meanings generated. In addition to the lexical-semantic structural work (ANTUNES, 2009), the game provides possibilities for expanding the linguistic repertoire, thus helping to develop reading comprehension and grammatical studies in a more contextualized way. Our theoretical foundation also includes Red (2012), Xavier (2013) and Leffa (2013), with contents related to the exploration of multiletrations and computational technologies in the classroom, Antunes (2007) and Bakhtin (2003), regarding teaching of the language in a context of interaction, Travaglia (2006) and Neves (2002), who carry ways of grammatical teaching with a view to the use and, finally, Ilari (2008) and Amaral (2016), dealing with the part related to semantics lexical. We have the prospect that the product in development will bring to the students of basic education, with a whole, opportunities of interaction so that they reach not only the understanding of uses of the grammar category of adverbs, but also they can better understand the ideas of the text literary. Thus, in a continuum of understanding, we will be favoring the settlement and spreading of language education.